Sago Sep: traditional food sources in eastern indonesia and their potential as alternative foods for athletes - Akhmad Kadir; Suharno Suharno; Reawaruw Reawaruw; Aisyah Ali; Miftah Fariz Prima Putra (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Food sources around the world depend on the local availability in nature. In Indonesia, particularly in the eastern part, one of the naturally and locally available food sources is sago, which is processed into various traditional foods to meet the community’s daily needs. Aside from fulfilling the demand for food, sago is also culturally valuable. This study examines sago processing into traditional cuisines in the southern part of Papua, Indonesia, with data collected through a survey. The results show that the indigenous Marind Anim people process sago into different traditional foods: papeda, roasted sago or sago plates, and sago sep. Sago sep is a traditional food of the Marind Anim tribe commonly found in the lowland areas of Merauke. Meanwhile, Papeda and sago plates are influenced by the migrant community consisting of the northern Papuan and Maollucan indigenous peoples. Sago Sep’s types are sago sep Teta, Komabo, Nggalamo, Ebayak, Kwetahuk, and Sinoli, distinguished based on the additional constituent ingredients. The local people of Marind Anim still depend on sago to fulfill their food needs. They harvest sago growing naturally in the environment and turn it into foods such as sago sep, papeda, and sago plates. Apart from that, sago can be an alternative food source for athletes, especially in eastern Indonesia, because of its high carbohydrate and calorie content, although it needs to be combined with other foods to support athletes' energy needs.